Smart marketing with the internet of things - Simoes, Dora, 1970-; Barbosa, Belem, 1971-; Filipe, Sandra, 1973- (Business Science Reference, 2019)
"This book provides knowledge and skills that marketers need to act in the internet of things era. It focuses on the implications of the internet of things on marketing and provides cues on how to deal with its opportunities and challenges"--